Self-inflicted dermatoses: case report and review - Brana, Gabriela; Bollea Garlatti, María Luz; Staiger, Hernán; Torre, Ana Clara; Martínez Piva, María Manuela; Kowalczuk, Alicia; Mazzuoccolo, Luis Daniel (Revista del Hospital Italiano de Buenos Aires, 2018)
Self-inflicted dermatoses are a frequent cause for consultation and represent a diagnostic and therapeutic challenge. They are characterized by the conscious or unconscious self-generation of cutaneous lesions in the context of complex psychiatric disorders. We report the case of a patient who consulted at the dermatology department with two months history of irregular and superinfected ulcers located on the face. This case represented a diagnostic difficulty since only from an exhaustive interrogation and complementary examinations, which ruled out other pathologies, we arrived at the diagnosis of self-inflicted ulcers in the context of psychiatric pathology that required interdisciplinary management
Keywords: somatoform disorders; factitious disorders; medically unexplained syndrome; mental disorders